Industrial training report: Maybank. Special project:The impact of foreign direct investment on unemployment in Malaysia - Mohd Jawi, Maizatul Najihah (Universiti Teknologi MARA, Perlis, 2024)
During my internship at Maybank, from March 1, 2024, to August 9, 2024, I served as a Customer Service Intern, gaining firsthand experience in delivering exceptional customer support and managing client relationships within a leading financial institution. This role enabled me to develop a comprehensive understanding of Maybank's customer service operations and the essential skills required to excel in a dynamic, client-facing environment. My responsibilities included assisting customers with inquiries, handling transactions, and providing guidance on Maybank's various products and services, all of which contributed to enhancing my communication and interpersonal skills. Throughout the internship, I had the opportunity to work alongside experienced professionals who provided valuable mentorship and guidance. I was involved in initiatives to improve customer satisfaction, including gathering and analyzing customer feedback to identify areas for service enhancement. This experience allowed me to contribute to the development of strategies aimed at optimizing customer experiences and ensuring that Maybank continues to meet the evolving needs of its clientele. Additionally, I participated in training sessions that deepened my understanding of the bank's operations and compliance requirements, further equipping me with the knowledge to assist customers effectively. Overall, my internship at Maybank was an invaluable experience that solidified my interest in pursuing a career in the financial services industry, specifically within customer service roles. The skills and insights I gained during this period have prepared me to handle the challenges and opportunities that come with a career in banking. I am eager to apply my enhanced customer service capabilities and financial acumen to future roles, contributing positively to the organizations I work with and furthering my professional development in the financial sector.